Controlled Digital Lending of Video Resources: Ensuring the Provision of Streaming Access to Videos for Pedagogical Purposes in Academic Libraries - Lear, Christian (Journal of Copyright in Education & Librarianship, 2022)
This article examines a current crisis within media librarianship regarding the challenges for academic libraries in providing streaming access to video resources despite the growing need for users to have streaming access. The article discusses this crisis largely within the context of COVID-19 (Coronavirus Disease of 2019) and how the pandemic has exacerbated the problem. This article also posits a possible solution to the issue through the application of controlled digital lending (CDL) to video resources for a pedagogical purpose. The article demonstrates the extent of the crisis, examines how other media librarians have addressed the problem, and shows the limitations to the solutions that have so far been offered. It then broadly discusses the concept of CDL and how this practice could be applied to video resources to address the frequent inability of libraries to provide streaming access to videos.